Identifying Stroke Caregivers’ Coping Strategies: The Smile that has Struggled through the Tears-A Mixed-Method Research Approach - Md Mizanur, Rahman; Norliza, Suut; Zabidah, Putit; Mohamad Taha, Arif; Asri, Said; Mohd Raili, Suhaili; Mohd, Fadzillah; Zainab, Tambi; Ling, How Kee (Bangladesh Academy of Sciences., 2024)
Background: Sudden stroke had caused the caregivers minimal time to prepare for their role as carers. Some stroke caregivers were overwhelmed to adjust and accept new responsibilities. They need to reorganise their functions and establish new daily life routines in response to the chronic illness that happens with stroke survivors. Objective: This study aimed to determine and explore coping strategies employed by stroke caregivers. Methods: This mixed-method study involved 32 stroke caregivers from a community-based stroke rehabilitation centre in Kuching, Sarawak. Results: From quantitative analysis, most stroke caregivers employed problem-focused coping strategies (mean=56.66, SD=10.79), followed by emotion-focused coping strategies (mean=55.63, SD=10.29) in confronting the challenges of caring for stroke survivors. Data from qualitative findings revealed eight themes of coping strategies: adjustment to daily life, selfmotivation, sharing with other people, acceptance, avoiding thinking about the problem, hoping stroke survivors will get better, emotion suppression and self-blame. Conclusion: This study’s outcomes provide crucial information about the burdens held by stroke caregivers when taking care of stroke survivors. Stroke caregivers need to adapt better and suitable coping strategies. This will prevent them from becoming overwhelmed by the accumulated stress from caring burdens. The long-term effect of coping strategies should positively assist stroke caregivers in managing the burdens effectively and fostering satisfaction in their life.